A reciclagem e o brincar como práticas de ensino em um centro de educação infantil municipal de São Mateus/ES - Salvador, Vitor Vasconcelos (2024)
Early childhood education is a space of rights and experiences. It is a rich phase of knowledge, assimilation, closeness and learning. The school, represented by a Municipal Early Childhood Education Center in this research, is the one that mediates this process through its teachers, contributing to the integral and total development of children in their social, cultural, cognitive and community aspects. It is the school that will seek to guarantee these rights, together with the family and other competent bodies. The initial provocation behind the research was the search for answers and new pedagogical approaches. The issue of waste disposal and forms of play, although very different problems, can be brought closer together, becoming allies in solving problems and building projects. Within the theme of rights and processes, play is a means of constructing the child. Through play, children learn, teach, interact, get to know each other, express themselves, socialize and achieve autonomy. In fact, they learn by playing and play by learning. Allied to this, this study also emphasized the right to live in a sustainable world that reuses, rethinks and recycles, the right to a world with clean air, clean water, protected trees and treated and/or reused waste. All of this is also a guarantee of rights. It is from this point of view and with an eye to these needs to promote a sustainable pedagogical approach with children and for children, a way of being a school for and with children, that this qualitative research took as its locus a Kindergarten Unit in a neighborhood on the outskirts of São Mateus, with the aim of investigating the reality of a public school, how the children see the world around them, how they see what is done with waste unfolding, and finally, to encourage them to reflect and become aware of and take a stance on everything that has been done to the environment, culminating in the construction of toys from reused material, generating new ways of playing. Conversation circles were used as a methodology and enriched the debate. The proposal brought together the idea of sustainability and play through the transformation of scrap metal into toys, but above all, it sought to transform the way of thinking and acting, leading the children to rethink their families' practices regarding the disposal of waste. Vygotsky and Ausubel inspired this journey, which, full of playful proposals and conversation circles, generated research, questioning, reflection and significant learning